2004
DOI: 10.1097/01.ccm.0000108875.35298.d2
|View full text |Cite
|
Sign up to set email alerts
|

Pain behaviors observed during six common procedures: Results from Thunder Project II*

Abstract: Because of the strong relationship between procedural pain and behavioral responses, clinicians can use behavioral responses of verbal and nonverbal patients to plan for, implement, and evaluate analgesic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
189
1
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(212 citation statements)
references
References 33 publications
4
189
1
18
Order By: Relevance
“…This finding aligns with the results of other research, indicating that routine ICU activities (eg, repositioning and suctioning) are a source of patients' distress [33][34][35] and that corresponding assessment and management of pain, agitation, and delirium are needed. 36 Although patients' discomfort during oral procedures has been examined in other populations of patients, [37][38][39] this issue in ICU patients has received limited attention.…”
Section: Discussionsupporting
confidence: 79%
“…This finding aligns with the results of other research, indicating that routine ICU activities (eg, repositioning and suctioning) are a source of patients' distress [33][34][35] and that corresponding assessment and management of pain, agitation, and delirium are needed. 36 Although patients' discomfort during oral procedures has been examined in other populations of patients, [37][38][39] this issue in ICU patients has received limited attention.…”
Section: Discussionsupporting
confidence: 79%
“…Although increased blood pressure and increased cardiac rates were found to be associated with acute pain in previous studies, (24) other studies found that these physiological indicators are not suitable indicators for the presence of pain. (6,15) In this study, physiological indicators were recorded less frequently than behavioral indicators in nurses' notes, which was consistent with the findings of a previous study.…”
Section: Pain Assessmentmentioning
confidence: 87%
“…In order to guide extraction of narrative descriptions of pain assessment, a reference compendium of potential behavioral descriptors was compiled from published behavioral pain assessment tools. [7][8][9]11,19,20 Data abstractors were instructed to record verbatim all documentation potentially related to pain assessment and management, including ambiguous documentation. The abstractors excluded any reference to pain behaviors elicited during routine neurological assessment.…”
Section: Study Design Participants and Settingmentioning
confidence: 99%
“…Several behavioral pain assessment tools [7][8][9][10][11] are now available that facilitate detection of pain experienced by critically ill patients unable to communicate. Systematic pain assessment, with either patient self-reporting or use of behavioral pain assessment tools as appropriate, can improve patients' outcomes.…”
mentioning
confidence: 99%